2020
DOI: 10.1038/s41598-020-69636-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel microwire-based biosensor probe for simultaneous real-time measurement of glutamate and GABA dynamics in vitro and in vivo

Abstract: Glutamate (GLU) and γ-aminobutyric acid (GABA) are the major excitatory (E) and inhibitory (I) neurotransmitters in the brain, respectively. Dysregulation of the E/I ratio is associated with numerous neurological disorders. enzyme-based microelectrode array biosensors present the potential for improved biocompatibility, localized sample volumes, and much faster sampling rates over existing measurement methods. However, enzymes degrade over time. To overcome the time limitation of permanently implanted microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 80 publications
(184 reference statements)
1
32
0
1
Order By: Relevance
“…The parameters employed in the equation were: the number of electrons ( n = 1), Faraday constant (F = 96,485 C mol L −1 ), the concentration of [Fe(CN) 6 ] 4− = 5 × 10 −6 mol cm −3 , and the average diffusion coefficient value of the [Fe(CN) 6 ] 4− in 0.1 mol L −1 KCl = 5.38 × 10 −6 cm 2 s −1 [ 41 ]. The one-way ANOVA test was performed ( n = 3) with significance defined as p < 0.05 to check whether the device-to-device surface variation during the optimization of fabrication or analytical parameters—e.g., type of PLE, biEP and sec-IgG concentrations, serum dilution ratio, and time of exposition—was significant, as done in studies found in the literature [ 42 , 43 ]. Then, a two-tailed Students t -test with a confidence level of 95% was performed for pairwise comparisons.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…The parameters employed in the equation were: the number of electrons ( n = 1), Faraday constant (F = 96,485 C mol L −1 ), the concentration of [Fe(CN) 6 ] 4− = 5 × 10 −6 mol cm −3 , and the average diffusion coefficient value of the [Fe(CN) 6 ] 4− in 0.1 mol L −1 KCl = 5.38 × 10 −6 cm 2 s −1 [ 41 ]. The one-way ANOVA test was performed ( n = 3) with significance defined as p < 0.05 to check whether the device-to-device surface variation during the optimization of fabrication or analytical parameters—e.g., type of PLE, biEP and sec-IgG concentrations, serum dilution ratio, and time of exposition—was significant, as done in studies found in the literature [ 42 , 43 ]. Then, a two-tailed Students t -test with a confidence level of 95% was performed for pairwise comparisons.…”
Section: Methodsmentioning
confidence: 93%
“…Then, a two-tailed Students t -test with a confidence level of 95% was performed for pairwise comparisons. [ 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Eksitatör ve inhibitör ana nörotransmitterler arasındaki denge normal bir beyin fonksiyonu için elzemken, GABA/Glutamat imbalansı epilepsiyle yakından ilişkilidir. [22][23] PTZ enjeksiyonları sonrası hipokampusta GABA konsantrasyonunun azalmış olması literatürle uyumludur. [24][25] PTZ'nin beyinde GABA ve Glutamat konsantrasyonları üzerindeki etkisini, bu nörotransmitterlerin metabolizmasında yer alan glutamat dehidrogenaz ve GABA aminotransferaz gibi enzimlerin aktivitelerini etkileyerek gerçekleştirdiği ileri sürülmektedir.…”
Section: Discussionunclassified
“…This approach has proven useful for measuring neurotransmitter levels within in vitro neural models 261 and monitoring neural differentiation of stem cells. 262…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%